Psychophysiology of Suryanamaskara: A Narrative Review - Devi, Khundrakpam Geetarani; KV, Swathi; K, Archana; Devi, Oinam Babbychand Bash; Singh, Moirangthem Joychand; HM, Prajwal; S, Swathi; Yadav, Amshuman R (Indian Journal of Integrative Medicine, 2024)
Salute to the Sun, often known as the Sun Salutation, is a sequence of twelve yoga postures that are gently linked to one another. Sun-salutation, an age-old Indian tradition is known to promote physical, mental, and spiritual wellness by regulating physiological processes moderated by the Autonomic Nervous System. This narrative review, documents the psychological changes following practice of Surya Namaskara. The online database, PubMed, PubMed central, Google scholar were searched using keywords “Suryanamaskara” from 2013 to 2022 which yielded a total of 1670 studies, of which 18 studies were clinical trials. The review conclude that sun salutation is effective in providing physiological and spiritual health by affecting different system of human body based on body system ,spiritual and psychological concept.